Stakeholder Collaboration in Developing Sustainable Ecotourism in Badung - Hamka, .; Koesponco, Eddy; Anita, .; Cahyaningrum, Sri; Yusuf, Muhammad (KnE Social Sciences, 2022)
The main challenge in developing sustainable ecotourism in Indonesia is to maintain a balance of economic, socio-cultural, and environmental development. The emergence of problems in tourism development is due to the direction of policies that prioritize the economic aspect so that it has an impact on the destruction of environmental ecosystems and the erosion of local wisdom and culture. This study aims to assess stakeholder collaboration in developing sustainable ecotourism in Badung Regency, Bali Province. The research approach used is a qualitative and exploratory research design where the data are sourced from in-depth interviews, FGDs, and secondary data. The research paradigm adheres to a constructivist view, data analysis is inductive. The findings of this study indicate that there are initiatives from the government to support the private sector, the community, and environmental conservation although it is not yet optimal. The varied types of relationships among stakeholders still leave a lack of understanding in building mutual trust and interdependence. For this reason, it is necessary for the commitment of stakeholders, especially the government in the form of providing financial, coaching, and administrative support so that cooperation continues to be strengthened so that it can gradually improve collaboration and reduce community dependence on the government and encourage business independence without neglecting socio-cultural interests and environmental preservation. Further studies are needed to understand strategies that can drive appropriate initiatives that impact stakeholder understanding, mutual trust, and self-reliance of the private sector and local communities to develop sustainable ecotourism. Keywords: collaboration, stakeholder, sustainable ecotourism